High-risk pregnant women’s experiences of the receiving prenatal care in COVID-19 pandemic: a qualitative study - Kobra Mirzakhani (BMC Pregnancy and Childbirth, 2022)
Abstract Background Women with high-risk pregnancies are among the most vulnerable groups that require additional precautionary measures against the spread of COVID-19 plus receiving prenatal care. Yet, there is limited information on the status of prenatal care in women with high-risk pregnancies. The purpose of this study was to explore the experiences of women with high-risk pregnancies who were receiving prenatal care during the COVID-19 pandemic. Methods The present qualitative study was conducted on mothers with high-risk pregnancies from September 2020 to March 2021. Purposeful sampling continued until achieving data saturation. Ghaem, Ommolbanin, and Imam Reza in Mashhad, Iran served as the research environment. Face-to-face and semi-structured interviews were effective data collection methods. Each interview lasted between 20 to 45 min (on average 30). The total number of participants was 31. Data analysis was carried out simultaneously with data collection using the qualitative content analysis method developed by Granheim and Landman (2004). Results Following the reduction and analysis of data from women in high-risk pregnancies, as well as their perceptions and experiences with health services during the COVID-19 pandemic, eight subcategories and three main categories were identified, including 1) “Negative psychology responses,” 2) “Adoption behavior,” and 3) “Adjustment of health services in mutual protection.” Fear, anxiety, stress, feelings of loneliness, sadness, depression, guilt, doubt and conflict in receiving services were examples of negative psychological responses. The adaptive behaviors’ category reflected the behaviors of women with high-risk pregnancies in the context of the COVID COVID-19 pandemic. The Adjustment of health services in mutual protection indicated that health workers took preventive and protective measures against COVID-19, which, in addition to protecting themselves and their clients against COVID-19, gave women a sense of security. Conclusion Receiving prenatal care during the COVID-19 pandemic presents challenges for women with high-risk pregnancies, negatively impacting their psychological state and health-seeking behavior. Supportive and preventive care can ensure that women with high-risk pregnancies receive optimal prenatal care that focuses on COVID-19 prevention. We recommend implementing screening, psychological counseling, and education for women with high-risk pregnancies, as well as ensuring that they have access to women-centered health care services.